Seismic moment and recurrence: Microstructural and mineralogical characterization of rocks in carbonate fault zones and their potential for luminescence and ESR dating - Tsakalos, Evangelos; Kazantzaki, Maria; Lin, Aiming; Bassiakos, Yannis; Filippaki, Eleni; Takafumi, Nishiwaki (Journal of structural geology, 2018)
The important question of absolute dating of seismic phenomena has been the study of several researchers over the past few decades. The relevant research has concentrated on “energy traps” of minerals, such as quartz or feldspar, which may accumulate chronological information associated with tectonic deformations. However, the produced knowledge so far, is not sufficient to allow the absolute dating of faults. Today, Luminescence and Electron Spin Resonance (ESR) dating methods could be seen as offering high potential for dating past seismic deformed features on timescales ranging from some years to even several million years. This preliminary study attempts to establish the potential of three different carbonate fault zones hosting fault mirror-like structures, to be used in luminescence and ESR dating, based on their microstructural, mineralogical and palaeo-maximum temperatures analysis. The results indicated that the collected samples can be considered datable fault-rock materials, since they contain suitable minerals (quartz) for luminescence and ESR dating, have experienced repeated cataclastic deformation and have been subject to various physical and chemical processes as well as pressure and temperature conditions. •This study indicated that calcareous fault-rocks can be considered datable materials.•Fault slickensides have experienced repeated cataclastic deformation.•Fault slickensides have been subject to various physical and chemical processes.•Fault slickensides have experience high pressure and temperature conditions.•There is evidence of luminescence/ESR signal resetting of minerals in fault slickensides.